Exploring the Language Attitudes of the Tolaki Community in Kendari: A Comprehensive Sociolinguistic Analysis - Sain, Yuliyanah; Hermansyah, Sam (Journal of Languages and Language Teaching, 2025)
This study explores the language attitudes of the Tolaki people in Kendari City, Southeast Sulawesi, focusing on their perceptions of the Tolaki language in comparison to immigrant or dominant languages such as Indonesian. As a sociolinguistic investigation, the research examines how language pride, loyalty, and awareness influence language maintenance or contribute to language shift. The study targets all native speakers of the Tolaki language residing in Kendari, a city administratively divided into 10 sub-districts. A multi-stage sampling technique was adopted to ensure a representative sample. Stratified sampling was employed to select participants based on demographic factors such as age, gender, education, and occupation. In the first stage, six sub-districts—Abeli, Kendari, Poasia, Puwatu, Kambu, and Wua-wua—were chosen due to their high concentration of Tolaki speakers. A total of 322 respondents participated in the study. Data were collected using structured questionnaires to measure language attitudes, semi-structured interviews to explore deeper personal and cultural insights, and direct observation to assess actual language use in daily contexts. The quantitative data were processed using SPSS, while qualitative data were analyzed thematically. The findings revealed that language attitudes among Tolaki speakers—especially concerning pride in using the language, loyalty to its use, and awareness of its norms—were generally low. This decline in positive language attitudes, particularly among younger generations, has contributed to a noticeable language shift. The Tolaki language is increasingly marginalized in daily communication, indicating a weakening intergenerational transmission and a growing dominance of Indonesian in informal and public domains.